Psychology of a superpower : security and dominance in U.S. foreign policy - Fettweis, Christopher J. (Columbia University Press, 2018)
With the collapse of the Soviet Union, the United States was left as the world's sole superpower, which was the dawn of an international order known as unipolarity. The ramifications of imbalanced power extend around the globe--including the country at the center. What has the sudden realization that it stands alone atop the international hierarchy done to the United States? In Psychology of a Superpower, Christopher J. Fettweis examines how unipolarity affects the way U.S. leaders conceive of their role, make strategy, and perceive America's place in the world.Combining security, strategy, and psychology, Fettweis investigates how the idea of being number one affects the decision making of America's foreign-policy elite. He examines the role the United States plays in providing global common goods, such as peace and security; the effect of the Cold War's end on nuclear-weapon strategy and policy; the psychological consequences of unbalanced power; and the grand strategies that have emerged in unipolarity. Drawing on psychology's insights into the psychological and behavioral consequences of unchecked power, Fettweis brings new insight to political science's policy-analysis toolkit. He also considers the prospect of the end of unipolarity, offering a challenge to widely held perceptions of American indispensability and asking whether the unipolar moment is worth trying to save. Psychology of a Superpower is a provocative rethinking of the risks and opportunities of the global position of the United States, with significant consequences for U.S. strategy, character, and identity.